The Extent of application the principles of total quality management in Improving health services in hospitals exploratory study at Al-kindi hospital / Baghdad health department Rusafa - شاكر احمد (Journal of Economics and Administrative Sciences, 2025)
Abstract : The purpose of the subject of Total quality management is an important management style in organizations including hospitals through the achievement of this method of success in the administration to include this approach describes the provision of health services and make adjustment and suggestions that help to improve the quality of health care on an ongoing basis . Hence the idea of the study to shed light on the reality of the application of principles of Total quality management and to highlight the quality of health services provided in al-kindi hospital / Baghdad health department rusafa and the staff at the hospital were included to find out the application requirements of Total quality management. The problem of the study was identified in the identification of the most important reasons that iead to follow the style of Total quality management in improving health services and depended on the collection and organization of theoretical information was based on a survey methodology as a curriculum that combines more than one research style into one . the statistical methods have been followed for the purpose of testing hypotheses of stability and testing kolmogorov- smirnov Repetitions ,percentages ,arithmetical averages , standard deviations and analysis of mono –variance and one of the most important solutions has been reached weak commitment of the senior management of the hospital in support of quality effects and weak application as a result of the lack of training courses for the implementationof quality programs and lack of focus on work in the embodiment the principles of Total quality management and the most important recommendations are the success of the application the principles of Total quality management depends necessarily on the extent of the senior managements conviction first and commitmentand and the need to emphasize more efforts to promote concepts and the principles of Total quality management and try to establish them in alarge extant to the workers in al-kindi hospital / Baghdad health department Rusafa to reach ahigh level of quality of services workers.